TRPV4-induced Müller cell gliosis and TNF-α elevation-mediated retinal ganglion cell apoptosis in glaucomatous rats via JAK2/STAT3/NF-κB pathway - Qian Li (BMC, 2021)
Abstract Background Glaucoma, the leading cause of irreversible blindness worldwide, is a type of retinal disease characterized by the selective death of retinal ganglion cells (RGCs). However, the pathogenesis of glaucoma has not been fully elucidated. Transient receptor potential vanilloid 4 (TRPV4) is a pressure-sensitive and calcium-permeable cation channel. TRPV4 is widely distributed in the retina and its sustained activation leads to RGC death; indicating that TRPV4 may be a possible target for glaucoma treatment. Here, we investigated the effects of TRPV4 on RGC apoptosis in a rat model of chronic ocular hypertension (COH), then examined the mechanism underlying these effects. Methods The COH model was established by injection of micro-magnetic beads into the anterior chamber of adult male rats. The expression levels of TRPV4, glial fibrillary acidic protein, and inflammatory factors were assessed by immunohistochemistry and immunoblotting. RGC apoptosis and visual dysfunction were evaluated by TUNEL assay and photopic negative response. Functional expression of TRPV4 was examined by electrophysiology and calcium imaging. Real-time polymerase chain reaction and immunoblotting were employed to investigate the molecular mechanism underlying the effects of TRPV4 on tumor necrosis factor-α (TNF-α) release. Results We found that TRPV4 played an essential role in glaucoma, such that high levels of TRPV4 expression were associated with elevated intraocular pressure. Furthermore, TRPV4 activation was involved in glaucoma-induced RGC apoptosis and RGC-related reductions in visual function. Mechanistic investigation demonstrated that TRPV4 activation led to enhanced Müller cell gliosis and TNF-α release via the JAK2/STAT3/NF-kB pathway, while TRPV4 inhibition could reverse these effects. Finally, TRPV4 activation could lead to elevated expression of TNF receptor 1 in RGCs, while inhibition of TNF-α could reduce TRPV4-mediated RGC apoptosis. Conclusions TRPV4 activation induces Müller cell gliosis and TNF-α elevation via the JAK2/STAT3/NF-κB pathway, which may exacerbate RGC apoptosis in glaucoma; these results suggest that TRPV4 can serve as a therapeutic target in glaucoma treatment.